Resiliensi Komunitas Agama Baha’i Di Masa Pandemi: Perspektif Antropologi - Amanah Nurish (LIPI Press, 2021)
This research paper aims to explore the Indonesian Baha’is community and its conceptual discourse on resilience and social solidarity in religious actions during global pandemic of covid-19. Although the Baha’i faith is not registered as an official religion in Indonesia like Islam, Christianity, Buddhism, Hinduism, etc., the Baha’is community and its religious as well as social movement during covid-19 is interesting to analyze. As a new world religion promoting the principle and the moral value on unity in diversity, Baha’is community in Indonesia started to organize digital activism to build solidarity among interfaith and religious minority groups like penghayat kepercayaan. Religion and solidarity in this context refer to a Germany sociologist, Emile Durkheim (1858-1917), on his functionalism perspective stating that religion must have social function and solidarity. Durkheim demonstrated the function of religion can be understood as collective action as moral value in our society. Religion not only has a meaning but also a function, which is collectively built by society, based on collective consciousness. By digital ethnographic approach, this research paper tries to examine how the Baha’is community and other minority groups in Indonesia cope the global pandemic of covid-19 while activities have moved to virtual and digital space. It is also interesting to perceive how resilience of the Baha’is community in existing religious dakwah throughout digital activism. The Baha'is community has shown resilience by not only protecting their own groups, but also for the larger community by distributing assistance and fostering social cohesion regardless of ethnicity, language, race, or religion on the basis of humanity.